Type, Memory, and Meaningful Form - Wendy Ornelas (Oz, 1990)
Type, as you will see, is a device that links the past with the future. Typology, according to Quatremere de Quincy, is "rooted in the nature of the region, in historical notions, and in the monuments of the developed art themselves."